Validation of the Malay version of eating disorder examination-Questionnaire 6.0 (EDE-Q 6.0) among undergraduate students: a study protocol - Mohd Taib, Nasehah; Abdul Khaiyom, Jamilah Hanum (Malaysian Psychiatric Association, 2019)
The present study aims to examine the reliability, validity, and factor structure of the Malay version of Eating Disorder ExaminationQuestionnaire 6.0 (EDE-Q 6.0). It is essential to have a locally developed instrument that can screen eating disorders for early detection. With proper screening, the individual with eating disorders will be able to receive early intervention. However, to develop a new screening test, a huge investment of time and resources is required. Thus, this study plans to adapt the latest EDE-Q 6.0 because it is in concordance with the ‘gold standard’ assessment for eating disorder. In order to reach the objective, this study will use survey research design and will recruit undergraduate students (N=400) from different faculties in one of the local public university in Klang Valley, Malaysia. The current study will adhere to procedure of the best practice for test adaptation as suggested by the International Test Commission (ITC) Guidelines Second Edition (2016) in validating Western based measure into different language or culture. The data will be analysed using IBM SPSS Statistics Software for descriptive and inferential statistics. Malay EDE-Q 6.0 is expected to have acceptable reliability and validity with similar factor structure to the theoretical four components of the EDE-Q 6.0. With the expected results, this study hopes to contribute to the body of knowledge in continuous empirical examination of psychometric properties of EDE-Q 6.0, at the same time, able to assist clinicians during their practical works in detecting eating disorders so that early intervention can be carried out.